Generation of an RCVRN-eGFP Reporter hiPSC Line by CRISPR/Cas9 to Monitor Photoreceptor Cell Development and Facilitate the Cell Enrichment for Transplantation - Guan, Yuanyuan; Wang, Yuan; Zheng, Dandan; Xie, Bingbing; Xu, Ping; Gao, Guanjie; Zhong, Xiufeng (Frontiers in Cell and Developmental Biology, 2022)
Stem cell-based cell therapies are considered to be promising treatments for retinal disorders with dysfunction or death of photoreceptors. However, the enrichment of human photoreceptors suitable for transplantation is highly challenging so far. This study aimed to generate a photoreceptor-specific reporter human induced pluripotent stem cell (hiPSC) line using CRISPR/Cas9 genome editing, which harbored an enhanced green fluorescent protein (eGFP) sequence at the endogenous locus of the pan photoreceptor marker recoverin (RCVRN). After confirmation of successful targeting and gene stability, three-dimensional retinal organoids were induced from this report line. The RCVRN-eGFP reporter faithfully replicated endogenous protein expression of recoverin and revealed the developmental characteristics of photoreceptors during retinal differentiation. The RCVRN-eGFP specifically and steadily labeled photoreceptor cells from photoreceptor precursors to mature rods and cones. Additionally, abundant eGFP-positive photoreceptors were enriched by fluorescence-activated cell sorting, and their transcriptome signatures were revealed by RNA sequencing and data analysis. Moreover, potential cluster of differentiation (CD) biomarkers were extracted for enrichment of photoreceptors for clinical applications, such as CD133 for the positive selection of photoreceptors. Altogether, the RCVRN-eGFP reporter hiPSC line was successfully established and the first global expression database of recoverin-positive photoreceptors was constructed. These achievements will provide a powerful tool for dynamically monitoring photoreceptor cell development and purification of human photoreceptors, thus facilitating photoreceptor cell therapy for the advanced retinal disorders.